Pengaruh Musik Sebagai Media Pembelajaran Pendidikan Agama Kristen Terhadap Pertumbuhan Iman Pelayan Altar - Rewah, Priskila Eunike; Wuwung, Olivia Cherly; Mailool, Jefri (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the effect of music as a learning media of Christian Education on the growth of faith of worship team members in GPdI region XXVI Kauditan. The type of this research is quantitative research with a causal associative type. The respondents of this study numbered 126 people, selected using simple random sampling technique. The instrument of this research is questionnaire consisting of 43 items. The instrument meets the validity and reliability requirements, with Aiken's content validity coefficient scoring ≥ 0.78 and the reliability coefficient scoring more than 0.70. Data analysis is conducted using simple linear regression. The results of the study show that music as a learning media for Christian Education affects faith growth by 50.5 percent. Thus, it is proven that music as a learning media of Christian Education affects the faith growth of team members in GPdI region XXVI Kauditan. Therefore, churches in teaching Christian Education can use music as a media to enhance faith growth of team members in long-term programs in each church.